Murine mucopolysaccharidosis type VII: long term therapeutic effects of enzyme replacement and enzyme replacement followed by bone marrow transplantation. - Sands, M S (1997)
We demonstrated previously that short term administration of recombinant beta-glucuronidase to newborn mice with mucopolysaccharidosis type VII reduced lysosomal storage in many tissues. Lysosomal storage accumulated gradually after cessation of enzyme replacement therapy. Mice alive at 1 yr of age had decreased bone deformities and less lysosomal storage in cortical neurons. Here we compare the effects of long term enzyme replacement initiated either at birth or at 6 wk of age, and of enzyme administration initiated at birth followed by syngeneic bone marrow transplantation (BMT) at 5 wk of age. Several mice from each treatment group lived to at least 1 yr of age. Liver and spleen samples had beta-glucuronidase levels ranging from 2.4 to 19.8% of normal and showed a parallel decrease in lysosomal storage. The combination of enzyme replacement therapy followed by BMT reduced lysosomal distension in meninges, corneal fibroblasts, and bone when compared with treatment with enzyme alone. Mice treated at birth had less lysosomal storage in some neurons of the brain and the skeletal dysplasia was less severe when compared to mice whose treatment was delayed until 6 wk of age. We conclude that both enzyme replacement alone and early enzyme replacement followed by BMT have long term positive effects on murine mucopolysaccharidosis type VII. In addition, treatment started at birth is far more effective than treatment initiated in young adults.